1986
DOI: 10.1093/ajcp/85.5.636
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukemia of Burkitt’s Type (L3 ALL) with 8;22 and 14; 18 Translocations and Absent Surface Immunoglobulins

Abstract: A 57-year-old woman presented with L3 acute lymphoblastic leukemia demonstrating typical Burkitt's type morphology. Cytogenetic analysis revealed one of the variant translocations seen in Burkitt's lymphoma [t(8;22)] and a 14;18 translocation. Surface marker data at presentation and at autopsy demonstrated several B-cell markers, but absent surface immunoglobulins. The case presented here reveals a possible cytogenetic link between Burkitt's lymphoma and follicular center-cell lymphoma, and illustrates a varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…The implication of band 8q24 is the rule, found in 20 of the 24 cases. The frequency of variant Burkitt's translocation t (8;22) 8,9,12,14 in this context is noteworthy 9 but this region could also be implicated in t(8;14), 6, 7, 9, 10, 11 in t(8;9)(q24;p13) 13,16 or, as in our patient 1, in complex translocation t(8;14;18)(q24;q32;q21). 15 As in our patient 2, molecular implication of c-MYC could not always be demonstrated, 10,13 especially in translocations not involving immunoglobulin genes.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The implication of band 8q24 is the rule, found in 20 of the 24 cases. The frequency of variant Burkitt's translocation t (8;22) 8,9,12,14 in this context is noteworthy 9 but this region could also be implicated in t(8;14), 6, 7, 9, 10, 11 in t(8;9)(q24;p13) 13,16 or, as in our patient 1, in complex translocation t(8;14;18)(q24;q32;q21). 15 As in our patient 2, molecular implication of c-MYC could not always be demonstrated, 10,13 especially in translocations not involving immunoglobulin genes.…”
Section: Discussionsupporting
confidence: 57%
“…Immunophenotype study in these cases always revealed the presence of B cell-associated markers as CD10 and CD19 but some cases with a morphologic aspect of ALL L3 lacked cytoplasmic and membranous immunoglobulins. 6,8,9,10,12 This particular feature underlined by Gluck et al 8 was also found by Thangavelu et al, 9 who suspected a correlation with the presence of a t(8;14) associated with the t(14;18). All our cases expressed surface immunoglobulin with kappa light chains and were CD10 positive, all features consistent with Burkitt's lymphoma/leukemia or diffuse large-cell lymphoma.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…There have been 11 case reports of Burkitt-type leukemia (ALL-L3) in the literature with both the t(14;18) and variants of c-MYC (t(8;14) or t(8;22)). [13][14][15][16][17][18] By contrast, concurrent t(2;8) and t(14;18) is very rare and has been reported only once in a cell line created from a patient with chronic lymphocytic leukemia. 19 In this case, an immortalized cell line initially carried t(14;18) without t(2;8).…”
Section: Discussionmentioning
confidence: 99%